Belajar Literasi Dan Memupuk Rasa Percaya Diri Anak Di LSM KOPA, Medan Maimun - Ramadani Safitri; Agus Suriadi (Jurnal Pengabdian Kepada Masyarakat, 2023)
According to the KBBI, the meaning of literacy itself, as reported on the Ministry of Education and Culture's official website, is the ability to write and read.  Etymologically, the term literacy itself comes from the Latin "literatus" which means someone who learns.  In this case, literacy is closely related to the process of reading and writing.  Literacy activities in the learning phase aim to develop the ability to understand texts and relate them to personal experiences, think critically, and process communication skills creatively through activities responding to the texts of enrichment books and textbooks.  Literacy or literacy is a general term that refers to a series of individual abilities and skills in reading, writing, speaking, calculating and solving problems at a certain level of expertise required in everyday life.  Benefits of literacy Expanding insight and knowledge.  Sharpen the ability to capture and understand information from reading.  Literacy is not the same as reading.  Reading and books are the surface technical and physical forms of literacy.  The essence of literacy is how humans gain knowledge and learn to gain knowledge.  Raising self-confidence in children is a parent's responsibility, although cultivating self-confidence is not an easy job.  Apart from requiring patience and example, parents must be clever in creating an atmosphere that is conducive to growing children's self-confidence.  Especially an atmosphere that is able to foster a child's sense of self-esteem which must be understood together, by building a child's self-esteem it will not automatically be able to grow a child's self-confidence.  However, if a child has a healthy sense of self-esteem by knowing and being able to accept himself as he is, including all his limitations, then he will be able to feel ashamed of himself and see everything as part of the reality of life.